1984
DOI: 10.3109/17453678408992410
|View full text |Cite
|
Sign up to set email alerts
|

Heat caused by drilling cortical bone: Temperature measuredin vivoin patients and animals

Abstract: In vivo temperature measurements were performed at drilling in the femoral cortex of the rabbit, dog and man. In the clinical study the bone temperature was measured at fixation of a Richards plate to stabilize a pertrochanteric fracture. With a drill speed of around 20 000 rpm and saline cooling, temperatures of 40 degrees C in rabbits, 56 degrees C in dogs and 89 degrees C in patients were recorded at a distance of 0.5 mm from the periphery of the drill hole. The difference in temperature between the animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
216
0
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(248 citation statements)
references
References 3 publications
5
216
0
6
Order By: Relevance
“…They attributed this result to the difference in mean cortical thickness between the cadaveric (3 to 5mm) and bovine (7 to 9 mm) samples. Eriksson et al (Eriksson, Albrektsson et al 1984a) measured in vivo temperature elevations during drilling of rabbit, dog and human tibiae, encountering temperatures of 40˚, 56˚ and 89˚, respectively, under similar conditions. The differences in this study were also attributed to the difference in cortical thickness between species.…”
Section: Heat Generationmentioning
confidence: 99%
“…They attributed this result to the difference in mean cortical thickness between the cadaveric (3 to 5mm) and bovine (7 to 9 mm) samples. Eriksson et al (Eriksson, Albrektsson et al 1984a) measured in vivo temperature elevations during drilling of rabbit, dog and human tibiae, encountering temperatures of 40˚, 56˚ and 89˚, respectively, under similar conditions. The differences in this study were also attributed to the difference in cortical thickness between species.…”
Section: Heat Generationmentioning
confidence: 99%
“…Although we have used a higher drilling speed, this difference would not result in significant temperature elevation, as was previously demonstrated. [17][18][19][20][21][22][23] The duration of drilling in our experiment was <5 s which is shorter than the 30 s critical exposure reported by Lundskog. 22 Moreover, the thickness of rat cortical bone at distal femoral sites (1 mm) is much thinner than the thickness of human cortical bone.…”
Section: Surgical Preparation Of Bone-scaffold Interfacementioning
confidence: 83%
“…15 However, the focus of all these studies has been on the corresponding increase in temperature and thermal damage due to drilling the cortical bone. [16][17][18][19] The effect of drilling on trabecular bone was not studied, perhaps due to a priori assumption that temperature increase is less significant and hence less crucial in this less dense part of the bone. Indeed, an important effect of drilling trabecular bone might not be the increase in temperature, but the damage to the structure of adjacent trabeculae, which may have serious biological consequences.…”
mentioning
confidence: 99%
“…Earlier investigations have shown a reduction in drilling temperature by external cooling and high feed forces [13][14][15][16][17]. Another study indicated an increase in drilling temperature when using a blunt drill.…”
Section: Discussionmentioning
confidence: 99%